Pipistrellus pipistrellus - Toffoli, Roberto; Culasso, Paola; Locatelli, Andrea G.; Giraudo, Luca (Zenodo, 2016)
Pipistrellus pipistrellus (Schreber, 1774) Risk Level Europe: Least Concern - LC (Temple & Terry, 2007). Italy: Least Concern - LC (Rondinini et al. , 2013). This is the most common species present in the study area. It is found in 75.0% of the kilometric grid, in which the area was divided. It was identified using bioacoustics analysis and roosts survey. Furthermore, it was also caught in mist-nets up to an altitude of 2100 m. Five reproductive roosts were found with a minimum of 21 individuals up to a maximum of 50 and further 6 temporary roosts frequented by single individuals were also identified. In total 34 individuals (21 males and 13 females) were captured in foraging areas and above water bodies. Published as part of Toffoli, Roberto, Culasso, Paola, Locatelli, Andrea G. & Giraudo, Luca, 2016, Bats of Alpi Marittime Nature Park (North West Italy) and Site of Community Importance IT 1160056: distribution and status, pp. 3-13 in Natural History Sciences 3 (1) on page 10, DOI:10.4081/nhs.2016.254, http://zenodo.org/record/12523731